Pengaruh Citra Merek dan Harga Terhadap Keputusan Pembelian Toyota Rush Melalui Minat Beli Sebagai Variabel Intervening (Studi Pada Konsumen Toyota Rush di Nasmoco Kota Semarang) - Kurniawan, Michael Aditya; Budiatmo, Agung (Universitas Diponegoro, 2020)
Abstract: Toyota is one of the outstanding car brands in Indonesia and also as a market leader in the automotive industry. The author conducted research to seethe effect of a brand image, price, purchase decisions and purchasing decisions. This type of research is explanatory research. The technique sampling using non-probability and purposive sampling with a sample of 100 respondents who are users and buyers of the Toyota Rush at Nasmoco Semarang. Research shows that brand image also has a positive and significant on buying interest, brand image also has a positive and significant on purchasing decisions, price also has a positive and significant on buying interest, prices also has positive and significant on buying decision, buying interest also has a positive and significant on purchasing decisions, there is also has a positive and significant effect of brand image on purchasing decisions through buying interest, there is also has a positive and significant effect of price on purchasing decisions through buying interest. Suggestions purchasing decisions is to improve the variable brand image, price and buying interest. In the aspect of brand image, companies need to strengthen the concept of